1992
DOI: 10.1007/bf02775064
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the markers related to collagen synthesis in the liver of chronically alcohol treated rats

Abstract: In order to clarify the roles of Ito cells in the development of alcoholic fibrosis, markers related to collagen synthesis in the liver were analyzed in chronically alcohol treated rats. The livers were obtained from rats fed a diet containing alcohol (alcohol group) and those fed a control diet (control group) for 4 weeks. Prolyl hydroxylase (PH) activity in the whole liver tissue did not differ in the alcohol and control groups. However, the activity in the isolated Ito cells was significantly higher in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In cultured rat liver cells, IV-C was mainly produced by Ito and endothelial cells (27). In rats treated for long periods with alcohol, prolyl hydroxylase activity in It0 cells increased and IV-C was clearly stained at the sinusoidal walls, without any evidence of hepatic fibrosis seen with routine connective tissue staining (28 results indicate that IV-C synthesis in Ito cells is increased by long-term alcohol consumption and that this increase may play an important role in the development of alcoholic fibrosis.…”
Section: Discussionmentioning
confidence: 80%
“…In cultured rat liver cells, IV-C was mainly produced by Ito and endothelial cells (27). In rats treated for long periods with alcohol, prolyl hydroxylase activity in It0 cells increased and IV-C was clearly stained at the sinusoidal walls, without any evidence of hepatic fibrosis seen with routine connective tissue staining (28 results indicate that IV-C synthesis in Ito cells is increased by long-term alcohol consumption and that this increase may play an important role in the development of alcoholic fibrosis.…”
Section: Discussionmentioning
confidence: 80%
“…These findings are consistent with the results of a study in rats by Gallo and Weinberg. 21 Takase et al 22 reported that there was clear immunohistochemical staining of type IV collagen along with the sinusoids in the livers of the alcohol-exposed fetuses, but weak staining reactions were seen in the control group. Also, they reported that total collagen synthesis, especially of type IV collagen, increased in cultured Ito cells and hepatocytes isolated from chronically alcohol-treated rats.…”
Section: Discussionmentioning
confidence: 95%